Neural tissue engineering: the influence of scaffold surface topography and extracellular matrix microenvironment. Issue 3 (8th December 2020) - Yang, Chun-Yi; Huang, Wei-Yuan; Chen, Liang-Hsin; Liang, Nai-Wen; Wang, Huan-Chih; Lu, Jiaju; Wang, Xiumei; Wang, Tzu-Wei
Abstract : Strategies using surface topography, contact guidance and biomechanical cues in the design of scaffolds as an ECM support for neural tissue engineering. Abstract : During nervous system development, an extracellular matrix (ECM) plays a pivotal role through surface topography and microenvironment signals in neurons and neurites maturation. Topography and microenvironment signals act as physical and chemical guiding cues, respectively, for neural tissue formation and reconstruction. Imposed surface topography can affect neural stem cells by promoting adhesion, spreading, alignment, morphological changes, and specific gene expression. Therefore, fabrication of a biomimetic construct or scaffold to support neurite outgrowth and axon extension is a crucial and common strategy for neural tissue regeneration. Here, we review recent developments in biomaterials modification for simulating the microenvironment to promote neural cell adhesion and growth. The subtopics include those of potential cellular mechanisms of topographical response, topography on cellular organization and function, contact guidance in neurite outgrowth and axon growth, ECM microenvironment as regulatory cues, as well as challenges and future perspectives of nerve conduits that are now in clinical trials and usage.